Rhetoric in sustainability report at PT Krakatau Steel Indonesia. - Rediyanto Putra; Sumadi Sumadi; Rahma Rina Wijayanti; Berlina Yudha Pratiwi; Oryza Ardhiarisca (Universitas Hayam Wuruk Perbanas, 2018)
This research was motivated by the implementation of Corporate Social Responsibility (CSR) activities at PT. Krakatau Steel, having suffered losses for five consecutive years. The objective of this study is to understand and prove the use of rhetorical communication techniques in the sustainability report by PT Krakatau Steel (public limited company). The data were taken from the sustainability report of PT Krakatau Steel from 2012 until 2016. This research uses qualitative approach with interpretive method. The analysis was done by means of a semiotic analysis of Charles Sanders Pierce. The result of semiotics studies, on the sustainability report of PT Krakatau Steel in 2012 until 2016 successfully proves that sustainability report is made as the company's rhetorical story. Rhetorical story on sustainability report of PT Krakatau Steel from 2012 to 2016 is structured for the purpose of three main objectives: (1) obtaining a form of recognition of legitimacy from external parties, (2) creating a positive image of the company conveyed to external parties, and (3) negative image disappearance